2014
DOI: 10.1039/c3pp50388g
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of transformations of the ultrafast electron transfer photoreaction mechanism in liquid solutions by the rate distribution approach

Abstract: Representation of the experimental reaction kinetics in the form of rate distribution is shown to be an effective method for the analysis of the mechanisms of these reactions and for comparisons of the kinetics with QC calculations, as well as with the experimental data on the medium mobility. The rate constant distribution function P(k) can be obtained directly from the experimental kinetics N(t) by an inverse Laplace transform. The application of this approach to kinetic data for several excited-state electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…There are several fitting procedures for recovery of the distribution of rate coefficients P ( k ) (a Laplace original) from the experimental kinetics N ( t )/ N (0) (a Laplace image). , In a general case, the direct inversion of the Laplace transform for recovering of the arbitrary probability densities of the rate coefficients P ( k ) has serious shortcomings, related to numerical instability, when the experimental data are intrinsically noisy. , This is related with a general property of inverse Laplace transform–the inverse transform of an experimental data set, which is inevitably incomplete and noisy, leads to ambiguity in P ( k ). A multitude of distribution functions will agree equally well with the experimental data.…”
Section: Experiments and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several fitting procedures for recovery of the distribution of rate coefficients P ( k ) (a Laplace original) from the experimental kinetics N ( t )/ N (0) (a Laplace image). , In a general case, the direct inversion of the Laplace transform for recovering of the arbitrary probability densities of the rate coefficients P ( k ) has serious shortcomings, related to numerical instability, when the experimental data are intrinsically noisy. , This is related with a general property of inverse Laplace transform–the inverse transform of an experimental data set, which is inevitably incomplete and noisy, leads to ambiguity in P ( k ). A multitude of distribution functions will agree equally well with the experimental data.…”
Section: Experiments and Methodsmentioning
confidence: 99%
“…Recently, some of us have shown that the nonexponential kinetics of ultrafast ET reactions in liquid solutions is related to the competition of several rate control factors: (1) the wide distributions of ET rate coefficients P ( k ET ) (for k ET ≈ 0.1–2 ps –1 ) caused by fluctuations of the electronic coupling matrix element ( V AD ) for reactant molecules located inside in the interior of the solvent shell; (2) reorganization of the medium and reactant molecules (in the range of the dielectric relaxation times); and (3) nonstationary diffusion of the reactant molecules (for k Diff [ Q ] ≈ 0.001–0.03 ps –1 ). In viscous solvents (η > 5 cP), some contribution of electron tunneling outside the interior of the solvent shell is also possible.…”
Section: Introductionmentioning
confidence: 99%
“…However, subsequent computational studies ,− , of quenching in neat conventional liquids point to a fundamental shortcoming of such a model for treating neat-solvent quenching. Instead of a single nearby partner, in neat redox-active liquids, the fluorophore is surrounded by multiple reactive partners.…”
Section: Resultsmentioning
confidence: 99%
“…The study of such systems has been a continuous interest area. In the literature, there are many works that report the interaction of a-diimine-ruthenium(II) ðRuðNNÞ 2þ 3 Þ complexes to different micellar media [5][6][7][8][9][10][11] as well as the influence of these interactions on the reactions with various compounds [12,13]. Moreover, the photochemistry and photophysics of a-diimine-chromium(III) ðCrðNNÞ 3þ 3 Þ complexes have been extensively studied in homogeneous systems [14,18], whereas there are, to the best of our knowledge, only a few works in micellar systems.…”
Section: Introductionmentioning
confidence: 99%